"SEGUNDA VEZ" Y "GRAFFITI", DE CORTÁZAR. UNA POÉTICA FANTÁSTICA PARA LA DESAPARICIÓN FORZADA. - Peris Blanes, Jaume (Revista Chilena de Literatura, 2020)
This article deals with the way Julio Cortázar used the poetics of the fantastic in two of his stories to give an account of the repressive mechanics of enforced disappearance in Argentina. He "translated to sensitive" the reports presented by various organizations and collectives of Human Rights in which Cortázar had participated, and in which the nature and functioning of the disappearing power in the military dictatorships of the Southern Cone was described in detail. In "Second time" and "Graffiti" Cortázar explored the possibilities of a non-standardized representation of political repression, which captured the paradoxical and dislocating character of the disappearance and alluded, in a complex way, to the profound affective and social impact of the policies of forced disappearance.